SUMO Pathway Dependent Recruitment of Cellular Repressors to Herpes Simplex Virus Type 1 Genomes - Cuchet-Lourenço, Delphine (Public Library of Science, 2011)
Components of promyelocytic leukaemia (PML) nuclear bodies (ND10) are recruited to sites associated with herpes simplex virus type 1 (HSV-1) genomes soon after they enter the nucleus. This cellular response is linked to intrinsic antiviral resistance and is counteracted by viral regulatory protein ICP0. We report that the SUMO interaction motifs of PML, Sp100 and hDaxx are required for recruitment of these repressive proteins to HSV-1 induced foci, which also contain SUMO conjugates and PIAS2β, a SUMO E3 ligase. SUMO modification of PML and elements of its tripartite motif (TRIM) are also required for recruitment in cells lacking endogenous PML. Mutants of PML isoform I and hDaxx that are not recruited to virus induced foci are unable to reproduce the repression of ICP0 null mutant HSV-1 infection mediated by their wild type counterparts. We conclude that recruitment of ND10 components to sites associated with HSV-1 genomes reflects a cellular defence against invading pathogen DNA that is regulated through the SUMO modification pathway.